1994
DOI: 10.1111/j.1476-5381.1994.tb14788.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of rat thoracic aorta induced by the Ca2+‐ATPase inhibitor, cyclopiazonic acid, possibly through nitric oxide formation

Abstract: 1 The effect of the Ca2+-ATPase inhibitor, cyclopiazonic acid (CPA), was studied on rat thoracic aortic ring preparations. 2 At concentrations above 0.3 JM, CPA induced relaxation in the arteries precontracted with phenylephrine. Removal of the endothelium abolished CPA-induced relaxation.3 The nitric oxide (NO) synthase inhibitor NG-nitro L-arginine (3-300 AM), the free radical scavenger haemoglobin (O.1-33 AM), the soluble guanylate cyclase inhibitor, LY83583 (0.1-10 JAM), each inhibited the endothelium-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
1
17
0
1
Order By: Relevance
“…In the rat aorta, it may promote Ca 2+ influx into endothelial cells to induce NO release from endothelial cells and then relax the aorta [18] . A different mechanism underlies the CPA-induced relaxation in mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat aorta, it may promote Ca 2+ influx into endothelial cells to induce NO release from endothelial cells and then relax the aorta [18] . A different mechanism underlies the CPA-induced relaxation in mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of agonist-sensitive Ca 2ϩ stores in either cell type results in elevation of cytosolic Ca 2ϩ concentration through SOC channels (SOCCs) (21). Elevation of Ca 2ϩ in endothelial cells activates endothelial nitric oxide synthase, yielding to endothelium-dependent vascular smooth muscle relaxation via nitric oxide (17,38,39). On the other hand, in the absence of intact endothelium, SOCCs also mediate Ca 2ϩ elevation in vascular smooth muscle (1,13,26,27,29,31,33).…”
mentioning
confidence: 99%
“…The endothelial NO synthase activity is dependent on cytoplasmic Ca 21 that has been suggested to be mostly derived from the extracellular space (1,2). Recent studies suggested that depletion of the Ca2+ store or endoplasmic reticulum (ER) could send an unidentified signal to the plasma membrane and allow the Ca 2+ to enter the cell in many types of non-excitable cells (3,4), including the endothelial cells in culture (5).…”
mentioning
confidence: 99%
“…6) and thapsigargin, that could empty the Ca 21 in the ER without any known interaction with receptor-mediated cell signaling (3). More recently, the model has been shown to be applicable to intact endothelial cells and to have an important functional significance: the Ca 2+-ATPase inhibitors induced an endothelial NOmediated vasorelaxation that was exclusively dependent on the extracellular Ca 21 (2). In this study, we investigated the CPA-induced relaxation and cyclic GMP formation in the rat aorta to obtain a clue to delineate the Ca 2+ entry mechanism in endothelial cells, with a special reference to tyrosine kinase that has been recently shown to be intimately involved in a diversity of cellular functions (7), including cellular Ca2+-handling (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation